ImplementasiPolitik Kebijakan Ruang Terbuka Hijau DKI Jakarta Berdasarkan Perda Nomor 1 Tahun 2012 Tentang Rencana Tata Ruang Wilayah Jakarta 2030 - Pengkuh Sidiq Waskito; Edi Santosa; Puji Astuti (Journal of Politic and Government Studies, 2015)
Spatial policy of Jakarta is one of the policies that are particularly vulnerable to irregularities in the implementation. Depletion of the presence of green open space to be one proof of how the results of the implementation of spatial policy Jakarta from 1965-1985 Master Plan, General Plan 2005 Spatial and Spatial Planning Jakarta in 2010 it is run with no attention to aspects of green open space which ultimately to date This availability will be in the ratio of 9% of the entire area of Jakarta. Under these conditions, this study aims to determine thecommitment of the Government of Jakarta, including the role of communities in the implementation of development policies Jakarta green open space, which refers to the Jakarta Bylaw No. 1 of 2012 on Spatial Planning Jakarta 2030. The method of this research method qualitative descriptive data. The results of the study refers to the theory of George Edward III shows that the factor of communication, resources, structures birookrasi, and disposition indicates that the implementation of green open space is still not running optimally due to the persistence of the external and internal constraints. Keywords: Spatial Planning, Implementation, Green Open Space.